2016
DOI: 10.1186/s12906-016-1119-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine by 7427 Australian women with cyclic perimenstrual pain and discomfort: a cross-sectional study

Abstract: BackgroundTo assess the prevalence of cyclic perimenstrual pain and discomfort and to detail the pattern of complementary and alternative (CAM) use adopted by women for the treatment of these symptoms.MethodsData from the 2012 national Australian Longitudinal Study of Women’s Health (ALSWH) cross-sectional survey of 7427 women aged 34–39 years were analysed to estimate the prevalence of endometriosis, premenstrual syndrome (PMS), irregular or heavy periods and severe dysmenorrhoea and to examine the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 62 publications
3
45
0
2
Order By: Relevance
“…In fact, as reported by Fisher et al patients affected were significantly more likely to consult a CAM practitioner or use CAM products compared to women without the disease. 46 …”
Section: Other Medicationmentioning
confidence: 99%
“…In fact, as reported by Fisher et al patients affected were significantly more likely to consult a CAM practitioner or use CAM products compared to women without the disease. 46 …”
Section: Other Medicationmentioning
confidence: 99%
“…5 There has been increasing evidence that CM, including naturopathy, 5 is more commonly used by women, 6 particularly by those with reproductive conditions being a common reason for naturopathy use. 7 Menstrual irregularities, including dysmenorrhea, known as painful menstruation, and menorrhagia, defined as excessive heavy menstrual bleeding, 8 have varying prevalence rates. A WHO systematic review reported prevalence rates for dysmenorrhea, ranging from 1.7% to 97%, 9 while an Australian study identified a prevalence rate of 80%.…”
Section: Introductionmentioning
confidence: 99%
“…20 There is emerging evidence of the use of naturopathy in the management of acute and chronic diseases, 3 including female reproductive conditions such as pregnancy, 21 menopause, 22 and polycystic ovarian syndrome. 23 While recent evidence suggests that naturopathy is used by women with these and other reproductive conditions, 7,16,24 there is limited evidence on the naturopathic treatments used in clinical practice. Identifying the level of engagement from traditional and contemporary evidence in practice is important to understand current naturopathic practice and to provide a foundational base for assessing naturopathic treatment ef-fectiveness and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these treatments have drawbacks, including significant costs to users and the health system, some unacceptable side effects, interference with women's reproductive function and, importantly, for up to 40% of sufferers, a failure to address their symptoms . In response, many women have opted to use complementary and alternative medicine (CAM) – a range of diverse health‐related practices and products located predominantly outside the conventional medical curriculum and profession – to treat CPPD symptoms . In particular, women who experienced endometriosis and/or frequent premenstrual syndrome (PMS), irregular periods or dysmenorrhoea were significantly more likely to consult a naturopath or herbalist than women who did not suffer from these menstrual issues …”
Section: Introductionmentioning
confidence: 99%
“…In response, many women have opted to use complementary and alternative medicine (CAM) – a range of diverse health‐related practices and products located predominantly outside the conventional medical curriculum and profession – to treat CPPD symptoms . In particular, women who experienced endometriosis and/or frequent premenstrual syndrome (PMS), irregular periods or dysmenorrhoea were significantly more likely to consult a naturopath or herbalist than women who did not suffer from these menstrual issues …”
Section: Introductionmentioning
confidence: 99%